Myopia disease mouse models: a missense point mutation (S673G) and a protein-truncating mutation of the Zfp644 mimic human disease phenotype - Szczerkowska, Katarzyna I; Petrezselyova, Silvia; Lindovsky, Jiri; Palkova, Marcela; Dvorak, Jan; Makovicky, Peter; Fang, Mingyan; Jiang, Chongyi; Chen, Lingyan; Shi, Mingming; Liu, Xiao; Zhang, Jianguo; et al. (Cell & bioscience, 2019)
Zinc finger 644 (Zfp644 in mouse, ZNF644 in human) gene is a transcription factor whose mutation S672G is considered a potential genetic factor of inherited high myopia. ZNF644 interacts with G9a/GLP complex, which functions as a H3K9 methyltransferase to silence transcription. In this study, we generated mouse models to unravel the mechanisms leading to symptoms associated with high myopia. Employing TALEN technology, two mice mutants were generated, either with the disease-carrying mutation (Zfp644 S673G ) or with a truncated form of Zfp644 (Zfp644 Δ8 ). Eye morphology and visual functions were analysed in both mutants, revealing a significant difference in a vitreous chamber depth and lens diameter, however the physiological function of retina was preserved as found under the high-myopia conditions. Our findings prove that ZNF644/Zfp644 is involved in the development of high-myopia, indicating that mutations such as, Zfp644 S673G and Zfp644 Δ8 are causative for changes connected with the disease. The developed models represent a valuable tool to investigate the molecular basis of myopia pathogenesis and its potential treatment.
Keywords: Mouse model; Eye; Genetics; Zinc finger 644; Myopia; Vision